2020
DOI: 10.1101/2020.11.24.397273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network mapping of root-microbe interactions inArabidopsis thaliana

Abstract: Understanding how plants interact with their colonizing microbiota to determine plant phenotypes is a fundamental question in modern plant science. Existing approaches for genome-wide association studies (GWAS) are based on the association analysis between host genes and the abundance of individual microbes, failing to characterize the genetic architecture of microbial interactions that are thought to a determinant of microbiota structure, organization, and function. Here, we implement a behavioral model to qu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 80 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…These QTL are involved in cell‐wall integrity, plant immunity, and root and root hair development (Bergelson et al, 2019). By reanalyzing the same dataset, He et al (2021) identified hub fungi and bacteria that are critical for assembling the microbial community. Likewise, they identified 91 hub host QTL involved in plant growth and development, root growth, pathogen resistance, and abiotic stress resistance (He et al, 2021).…”
Section: Main Factors Affecting the Root Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…These QTL are involved in cell‐wall integrity, plant immunity, and root and root hair development (Bergelson et al, 2019). By reanalyzing the same dataset, He et al (2021) identified hub fungi and bacteria that are critical for assembling the microbial community. Likewise, they identified 91 hub host QTL involved in plant growth and development, root growth, pathogen resistance, and abiotic stress resistance (He et al, 2021).…”
Section: Main Factors Affecting the Root Microbiotamentioning
confidence: 99%
“…By reanalyzing the same dataset, He et al (2021) identified hub fungi and bacteria that are critical for assembling the microbial community. Likewise, they identified 91 hub host QTL involved in plant growth and development, root growth, pathogen resistance, and abiotic stress resistance (He et al, 2021). A recent study suggests that FERONIA (FER), a cell membrane receptor protein kinase, is involved in regulating microbiota structure.…”
Section: Main Factors Affecting the Root Microbiotamentioning
confidence: 99%
“…We calculate the degree of each node in a network. To reduce the bias, we statistically identify the hub taxa with the highest degree and closeness centrality [13,37]. Meanwhile, six network indices, including connectivity (Con), closeness (C(u)), betweenness(B(u)), eccentricity (E(u)), eigencentrality (G(u)), and Pagerank (P(u)) are calculated, as described previously [35].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we can map host genes for the topological architecture of microbe-microbe interactions and interdependence. Second, it has been increasingly clear that microbial traits are not only determined by key host QTLs, but also through their epistatic networks [37]. Network mapping can draw the host genetic landscape of microbial interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys with field‐collected samples are limited in their ability to draw conclusions about the biological function(s) of the root microbiota. This is due to the numerous interactions between and within the different microbial classes of the root microbiota, interactions with the plant host, and the influence of edaphic and other environmental parameters on microbial community composition and activity (Bulgarelli et al., 2013; Duran et al., 2018; He et al., 2021; Thiergart et al., 2020). This makes it almost impossible to disentangle these interactions and assign particular plant phenotypes to microbial services.…”
Section: Commentarymentioning
confidence: 99%